The Ethics of Citation in Patrick Modiano’s Dora Bruder and Georges Perec’s W ou le souvenir d’enfance - Roderick Cooke (Studies in 20th & 21st Century Literature, 2018)
This article compares the representations of the Holocaust in Georges Perec’s W ou le souvenir d’enfance (W or the Memory of Childhood) and Patrick Modiano’s Dora Bruder. I concentrate on the two authors’ use of citation, in both cases of texts written by victims of the deportations, and identify a respective ethics of citation in each work by drawing on Antoine Compagnon’s theory. Modiano’s is best characterized through the term ‘responsibility,’ a responsibility he urges the reader to share with him in memorializing the wartime past. In the case of Perec, ‘resonance’ describes the manner in which he articulates the two halves of his book, as well as the wider historical lessons of the Shoah, around a citation from David Rousset. I conclude by suggesting that the ethical distinction between responsibility and resonance is connected to the generational difference between the two writers, famous examples of (in Perec’s case) Susan Suleiman’s ‘1.5 generation’ and, in Modiano’s, Marianne Hirsch’s generation of postmemory.
Keywords: Perec; Modiano; Holocaust; Dora Bruder; W or the Memory of Childhood; Ethics; Citation; Compagnon; Suleiman; Hirsch